PRINSIP HUKUM PENYELESAIAN PELANGGARAN PASSING OFF DALAM HUKUM MEREK - Agung Sudjatmiko (Yuridika, 2010)
The trademark has an exclusive right. The rights are to use the trademarks and to give license to other people/party to use the trademarks. Without the license from trademarks owner, if someone else use the trademarks, it’s infringement. There are many kinds of infringement of trademarks that are similarity, passing off. Passing off is to use the trademarks wrongly and it’s has impact to loose other people. Passing off is one of the infringement of trademarks in a common law system. Passing off is a common law tort which can be used to enforce unregistered trademark rights. The tort of passing off protect the goodwill of trader from a misrepresentation that causes damage to goodwill. The law of passing off prevents one person from misrepresenting his or her goods or services as being the goods and services of the claimant, and also prevents one person from holding out his or her goods or services as having some association or connection with the plaintiff when this is not true.